Dampak Krisis Terhadap Ketenagakerjaan Indonesia - - Saliman (Universitas Negeri Yogyakarta, 2005)
The economic growth of Indonesian before the year 1997 was considerably rapid and able to bring Indonesia obtaining a notation as one of Asian tigers. The economic growth brought positive impact to the matters pertaining to manpower of Indonesia. In 1997 the economic crises had befallen on Indonesia, the economic condition of Indonesia destroyed, business and industrial world were collapsed, signed by the bankruptcy of several companies. Even, there were some companies moved abroad, seeking new countries that had lower costs of production as home base. The impact of the crisis was many labor force lost their employment. The severance of working relation (PHK) was undertaken for the sake of efficiency so that the production could be run. On the other side, new job seekers emerged to compete in obtaining work field. The accumulation of the severance of working relation (PHK) and new labor force results in the increasing number of unemployment. Meanwhile the absorption power of work field was considerable limited due to the lack of opening new business.Ironically, there were various job vacancies unoccupied. The vacancies were still unoccupied since many job seekers graduating from Indonesian educational institution lacked expertise, skills and professionalism demanded. The educational institution had merely been able to pass unprepared labor force. Consequently, many educated unemployed could not be absorbed in field of work. There shall be many potential negative impacts due to the educated unemployment. Therefore, it necessitated real efforts in educational world to prepare its graduates so that they would be absorbed in work field, for example by the reevaluation of curriculum substance. The curriculum should be able to provide real experience for students. The entrepreneurship as exploratory subject should be taught since Senior High School. Furthermore, the apprentice program needed to be formulated by involving world of business and industry so that the implementation would give contribution significantly to the preparation process of labor force.